'Design for policy' from below: grassroots framing and political negotiation. Issue 4 (2nd October 2022) - Vaz, Federico; Koria, Mikko; Prendeville, Sharon
Abstract: Whilst design politics is an increasingly topical focus in the design field, in practice, design for policy has been normatively presented as a people-centric approach to public policymaking devoid of political or ideological agendas. Up to now, design for policy has exclusively been conceived as embedded within governmental structures, thus adopting a technocratic, internal, and top-down approach to, and understanding of, public policymaking. We argue that most often, this understanding and practice of design for policy establishes and mediates public problems from the standpoint of the government body addressing those problems. In this paper, we take a new and distinct point of departure to design for policy in which design is implicated in the practice of policymaking from below through processes of collective action. Design for Policy from Below moves from an intra-governmental lens to a negotiated exchange between social actors and government. In turn, this informs strategic collective action required to gain political support and leverage efforts to pressure power structures to acknowledge and adopt policy frames and options. To this end, we examine the conflictual power dynamics and negotiation-based approaches to influencing government policymaking processes and model the messy interplay between government-led policymaking and the activities of social innovators aiming at changing policy outcomes. Finally, we synthesize these insights into a conceptual model offering a novel viewpoint on how we can more critically understand the politics at play in design theory and practice engaged with policymaking.